Estimated Prevalence of Familial Hypercholesterolemia Among Egyptian Patients with Acute Coronary Syndromes; Analysis from The Cardiorisk Project. (8th October 2021) - Reda, Ashraf; Bendary, Ahmed; Elserafy, Ahmed Shawky; Farag, Elsayed; Mostafa, Tamer; Khamis, Hazem; Wadie, Moheb; Bendary, Mohamed; Elbahry, Atef; Salah, Rehab
Abstract: Aims: The prevalence of familial hypercholesterolemia (FH) in Egypt is largely un- known. We aimed to estimate the prevalence of FH among 3224 Egyptian patients with acute coronary syndromes enrolled from 2015 to 2018 in the nationwide cross- sectional cardioRisk project. Methods and Results: We applied the Dutch Lipid Clinic criteria for the diagnosis of FH on the available data recorded for the patients enrolled in the CardioRisk project. Two main criteria were applied: the presence of premature CAD (given 2 points in the Dutch criteria), and the categorized low density lipoprotein cholesterol (LDL-C) lev- els (given 1, 3, 5, or 8 points in the Dutch criteria according to the level). From a total of 3224 patients, 2743 patients had available LDL-C levels. Among those patients, when applying the abovementioned 2 criteria, we estimated that 472 patients had at least 'possible' FH (17.2% of the total population). Specifically, 4 patients had 'defi- nite' FH (0.1%), 7 patients had 'probable' FH (0.25%), and 461 patients had 'possi- ble' FH (16.8%). Conclusion: The estimated prevalence of at least 'possible' FH among Egyptian patients with ACS is 17%.